Rethinking the Impact of Hospital Strategy and Market Competition on the Use of Performance Measurement Dimensions in Private Healthcare Organizations: Evidence from Jordan - Aburumman, Ayman Mohammad; Ilias, Norazlina; Zin, Rosliza Mat (International Review of Management and Marketing, 2025)
With the ever-evolving waves of healthcare, these advanced synergies occur between Hospital Strategy (HS) and Market Competition (MC), and they significantly impact the use of Performance Measurement Dimensions (PMDs). The research would rather focus on the newly arising questions regarding hospital strategy, market competition, and the use of PMDs in the Jordanian private hospitals. Established empirically on a sample of 187 managers from 69 private hospitals in Jordan, in this article, PLS-SEM is utilized to extensively test the inherent relationships. The findings of this article conclusively demonstrate that market competition and hospital strategy both possess statistically significant impacts on the use of PMDs. These results ensure the reality of market competition and hospital strategic choices in healthcare organization operating performance, financial performance, and overall performance in the health sector in Jordan. The article then suggests creating more attention towards developing and coming up with the use of PMDs with a positive relationship with overall healthcare performance.